Transcriptional Plant Responses Critical for Resistance Towards Necrotrophic Pathogens - Birkenbihl, Rainer P.; Somssich, Imre E. (Frontiers in Plant Science, 2011)
Plant defenses aimed at necrotrophic pathogens appear to be genetically complex. Despite the apparent lack of a specific recognition of such necrotrophs by products of major R genes, biochemical, molecular, and genetic studies, in particular using the model plant Arabidopsis, have uncovered numerous host components critical for the outcome of such interactions. Although the JA signaling pathway plays a central role in plant defense towards necrotrophs additional signaling pathways contribute to the plant response network. Transcriptional reprogramming is a vital part of the host defense machinery and several key regulators have recently been identified. Some of these transcription factors positively affect plant resistance whereas others play a role in enhancing host susceptibility towards these phytopathogens.